Heart failure following transcatheter aortic valve replacement. (3rd August 2021) - Panagides, Vassili; Alperi, Alberto; Mesnier, Jules; Philippon, Francois; Bernier, Mathieu; Rodes-Cabau, Josep
ABSTRACT: Introduction : Over the past decade, the number of transcatheter aortic valve replacement (TAVR) procedures has increased exponentially. Despite major improvements in both device and successes, the rate of hospital readmission after TAVR remains high, with heart failure (HF) decompensation being one of the most important causes. Areas covered : This review provides an overview of the current status of HF following TAVR, including details about its incidence, clinical impact, contributing factors, and current and future treatment perspectives. Expert opinion : HF decompensation has been identified as the most common cause of rehospitalization following TAVR, and it has been associated with a negative prognosis. Multiple preexisting factors including low flow status, cardiac amyloidosis, myocardial fibrosis, multivalvular disease, pulmonary hypertension, coronary artery disease, and atrial fibrillation have been associated with an increased risk of HF events. Also, multiple post-procedural factors like the occurrence of significant paravalvular leaks, severe prosthesis-patient mismatch, and conduction disturbances have also contributed to increase this risk . Thus, reducing HF events in TAVR recipients would require a multifactorial and multidisciplinary effort including the optimization of the medical treatment and close follow-up and treatment of residual or concomitant valvular disease and conduction disturbance issues. Future studies in this challenging group of patients are warranted.